Development, Estimation and Validation of Lisinopril in Bulk and its Pharmaceutical Formulation by HPLC Method - V. Bhaskara Raju; A. Lakshmana Rao (E-Journal of Chemistry)
An accurate and precise HPLC method was developed for the determination of lisinopril. Separation of the drug was achieved on a reverse phase C8 column using a mobile phase consisting of phosphate buffer and methanol in the ratio of 35:65v/v. The flow rate was 0.8 mL/min and the detection wavelength was 215 nm. The linearity was observed in the range of 20-60 μ g/mL with a correlation coefficient of 0.9992. The proposed method was validated for its linearity, accuracy, precision and robustness. This method can be employed for routine quality control analysis of lisinopril in tablet dosage forms.